Engaging with the Bible in Visual Culture - Beaumont, Sheona (Enthalten in:Religion and the arts;Leiden : Brill, 1996;23(2019), 4, Seite 411-433;Online-Ressource, 2019)
Increasingly articulate contemporary art practices are engaging with biblical representation, revealing new relationships with religion through the availability of the word in image. Taking as exemplary the photographic publication of Adam Broomberg and Oliver Chanarin's Holy Bible (2013), this essay considers the evidence for their hermeneutics between image and word that is characterized by open awareness of and expansive participation in the (rereading of the) Bible. Discussing this engagement, I explore imagistic readings of the Bible through the artists' strategies of interpolation and repetition, as well as examining their chosen theme—catastrophe—for its revelatory power. Through the artists' self-reflexive hermeneutics of indeterminacy, I argue that the discussion of the return of religion in art needs attuning to this kind of specific practitioner experience: a hermeneutical circle of imaginative, dialogical, and dynamic interpretative positions in which the notion of indeterminacy is persuasive for interpretative grist, historical accountability, and theological horizon.
10.1163/15685292-02304004
Keywords: Archive of Modern Conflict; Bible; Broomberg; Chanarin; Christianity; Gadamer; Holy Bible; art history; hermeneutics; indeterminacy; photography; reception theory; theology; visual culture; visual culture criticism